Juvenile nasopharyngeal angiofibroma in a tertiary centre: ten-year experience - Tang, I.P.; Shashinder, S.; Gopala Krishnan, G.; Narayanan, P. (Stamford Publishing Pte Ltd / Singapore Medical Association, 2009)
JNA is a rare vascular benign tumour with highly exclusive persistence and recurrence, and typically affects adolescent boys. The management of JNA presents a challenge to ENT surgeons. Preoperative angiography and embolisation minimise intraoperative blood loss and the current shift in the treatment to endoscopic excision in selected lesions reduces perioperative morbidity.